In Vitro Assessment of The Bioactive Compounds and Anticancer Potential of Citrus medica Leaf Extract - Mikkili Indira; Karlapudi Abraham Peele; Srirama Krupanidhi; Kodali Vidya Prabhakar; K.B.S. Vimala; P. Satya kavya; Isani Sravya; T. C. Venkateswarulu (Tropical Life Sciences Research, 2023)
Citrus medica is a horticultural crop grown in different parts of the world. The plant leaves have medicinal importance in traditional medicine for the treatment of various diseases. The leaves are an underutilised part of the plant, despite having various bioactive compounds with health benefits, with phytochemical analysis having revealed the presence of flavonoids, fatty acids, alkaloids, terpenoids, glycosides, carbohydrates and phytosterols. The biochemical constituents were identified using Fourier-transform infrared spectroscopy (FTIR) and gas chromatography–mass spectrometry (GC-MS), which confirmed the presence of terpenoids, alcohols, alkanes, phytosterols and fatty acids. Among these, methyl 8, 11, 14-heptadecatrienoate is a linolenic acid, and ?-linolenic acid, trimethylsilyl ester and levulinic acid are the predominant compounds belonging to the omega-3 fatty acid group, which has known health benefits. Further, the antimicrobial activity of C. medica plant leaves were tested against certain food-borne pathogens and showed significant results. The minimum inhibitory concentrations ranged from 6.09 mg/mL to 390 mg/mL for bacterial organisms and 48.75 mg/mL to 390 mg/mL for fungal organisms. The antioxidant activity values were 300 ?g/mL and 450 ?g/mL by 2,2-diphenyl- 1-picrylhydrazyl (DPPH) and 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assay, respectively. The methanolic extract from the C. medica leaves also showed anticancer activity against MCF7 breast cancer cell lines, with an IC50 value of material for developing a healthy processed food such as nutraceuticals and functional foods.